1965
DOI: 10.1159/000457997
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Creatine Phosphokinase Activity of Chickens with Hereditary Muscular Dystrophy

Abstract: Plasma creatine phosphokinase activity (CPK) of hereditarily muscular dystrophic, normal and heterozygous chickens was determined using a method modified from that of Tänzer and Gilvarg. Plasma CPK activity of homozygous dystrophic chickens was significantly higher than that of normal chickens at 27-35 days of age and continued to rise to 131-134 days of age. At ten to 16 months of age plasma CPK activity was lower than at 131-134 days of age, yet still significantly higher than normal. Heterozygotes, sampled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1968
1968
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…This would be expected if serum CPK level is taken to be an indication of total muscle mass. A similar trend was shown in data reported by Holliday et al (8).…”
Section: Jury ( 5 )supporting
confidence: 91%
“…This would be expected if serum CPK level is taken to be an indication of total muscle mass. A similar trend was shown in data reported by Holliday et al (8).…”
Section: Jury ( 5 )supporting
confidence: 91%
“…Assay of CK for disease diagnoses include cardiac diseases (Wu, 2005), muscular dystrophy (Hsu, 2004) and inflammatory responses (Nirmalananthan et al , 2004). Biochemical analysis of serum CK activity has been developed since 1965, and most of these methods involve the assay of coupled enzymes or measurement of proton formation (Holliday et al , 1965). Under variable temperature and pH conditions, these methods would not be suitable to determinate the specific activities of the subisoforms of C. carpio M‐CK (Tanzer & Gilvarg, 1959; Mahowald et al , 1962; Rosalki, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is that pentobarbitone stimulates the dystrophic liver microsomal enzyme to a greater extent, thus enhancing its own rapid breakdown. Although elevated serum creatine kinase activity is a common clinical finding in humans and animals with muscular dystrophy (Okinaka et al, 1961 ;Eppenberger et al, 1964;Holliday et al, 1965;Munsat et al, 1973;Wilson et al, 1973), there are relatively few studies on dystrophic tissue creatine kinase (Hooton & Watts, 1965Roy, 1974). Our results indicate that both normal and dystrophic muscle contain about five times more creatine kinase than heart and brain tissue.…”
Section: Discussionmentioning
confidence: 48%
“…Elevated serum creatine kinase activity has been observed in muscular dystrophies of man (Okinaka, Kumagai, Ebashi, Sugita, Momoi, Toyokura & Fuji,, 1961;Munsat, Baloh, Pearson & Fowler, 1973), hamster (Eppenberger, Nixon, Baker & Homburger, 1964) and chicken (Holliday, Asmundson & Julian, 1965; Wilson, Linkhart, Walker & Nieberg, 1973). Because skeletal muscle is rich in creatine kinase, it has been suggested that the increase in the enzyme activity in dystrophic serum is due to 'leakage' of this enzyme through defective muscle membranes.…”
Section: Introductionmentioning
confidence: 99%